DEVELOPMENT ANS TRAINING OF A NEURAL NETWORK USING RAY - SEVERYNENKO, DANYLO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The document discusses the development and training of a neural network using the Ray framework, particularly focusing on a case study involving the Fashion MNIST dataset. Machine Learning (ML) has revolutionized various fields by enabling the processing and analysis of vast data sets with unprecedented accuracy and speed. It highlights ML's impact in healthcare, environmental science, and astrophysics, illustrating its ability to improve disease prediction models, climate change scenarios, and astronomical data analysis.Ray, an open-source Python framework, addresses several challenges associated with scaling ML applications. It simplifies the development of complex, distributed systems by providing a unified API that supports parallel task execution and large-scale model training. This framework efficiently manages tasks that require high-performance computing resources, such as real-time data processing and extensive simulations. Ray's scalability from single machines to clusters makes it indispensable in environments with fluctuating computational demands.The document details the technical process of setting up, training, and validating a neural network to recognize clothing images from the Fashion MNIST dataset using Ray. It covers the initial steps, such as importing necessary libraries and preparing the dataset, and outlines the architecture of the neural network built with various layers including ReLU and dropout for non-linearity and regularization to prevent overfitting. The training process involves distributed computing, highlighting Ray's capabilities in handling stateful and stateless computations across diverse hardware setups.Furthermore, Ray Train, previously known as Ray SGD, is part of Ray's ecosystem designed to simplify the scaling of deep learning and ML across multiple GPUs and nodes. It allows users to scale their ML models from a single computer to a distributed environment without significant code modifications, enhancing the developer's productivity by minimizing setup time for iterative development.The paper concludes with the successful development and training of a neural network using Ray, which demonstrates the framework's efficiency in enhancing the performance and reliability of ML systems across various industries. This study not only reaffirms Ray's role in advancing ML application scalability but also sets the stage for future explorations in distributed computing for artificial intelligence.
Keywords: Machine Learning; Ray Framework; Fashion MNIST; Neural Network; Distributed Computing; Scalability; Data Processing; Model Training; Deep Learning